Viabilidad Celular de Fibroblastos Orales Bioimpresos en Hidrogel de Gelatina de Metacrilato (2023)
analyze the cell viability of oral fibroblasts through different passages cells and their behavior in 3D printed matrices using a gelatin bioink methacrylate